(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2015)
From the very start, electronic language and video technologies have provided a free territory for expanding and reformulating multiple artistic itineraries, as well as a point of confluence for the most creative dialogue between different media. Raymond Bellour’s work has been significant in defining the role that video has played in the media context, describing it as a passeur between systems of old and new images, between the mobile and the immobile. Following the digital turn, it seems that the most obvious legacy of video in today’s digital system lies in the transfer, within the logic of computers, of that vocation for integration and intermediation which has always been acknowledged as its genetic characteristic. The computer becomes itself a passeur between the history of photography, the cinema and the experimental electronic world, increasing the possibility of interweaving influences, both practical and conceptual. The essay describes the work of some contemporary artists (Mittelstäd, Vogel, Klasmer), where the choice of a notably inter-media representation condenses the spirit of the history of photography and moving images, in a parabola that originates in pre-cinema to reach electronic experimentation and go towards the all-comprehensive logic of the metamedium-passeur.